Calcium levels modulate embryo yield in Brassica napus microspore embryogenesis - Calabuig-Serna, Antonio; Mir, Ricardo; Sancho-Oviedo, Daniel; Arjona-Mudarra, Paloma; Seguí-Simarro, Jose M. (Frontiers in Plant Science, 2025)
Calcium (Ca2+) is a universal signaling cation with a prominent role as second messenger in many different plant processes, including sexual reproduction. However, there is much less knowledge about the involvement of Ca2+ during in vitro embryogenesis processes. In this work we performed a study of Ca2+ levels during the different stages of microspore embryogenesis in Brassica napus, with special attention to how Ca2+ can influence the occurrence of different embryogenic structures with different embryogenic potential. We also performed a pharmacological study to modulate Ca2+ homeostasis during different stages of the process, using a series of Ca2+-altering chemicals (BAPTA-AM, bepridil, chlorpromazine, cyclopiazonic acid, EGTA, inositol 1,4,5-trisphosphate, ionophore A23187, W-7). This study shows that Ca2+ increase can be considered as an early marker of induction of microspore embryogenesis. Besides, Ca2+ levels are highly dynamic during microspore embryogenesis, influencing the final embryo yield. Increase of either extracellular or intracellular Ca2+ levels improves embryo yield without altering the proportion of highly embryogenic structures formed, which suggests that elevated Ca2+ levels increase the amount of microspores reaching the minimum Ca2+ threshold required for embryogenesis induction. Conversely, inhibition of Ca2+ uptake or signaling results in reduced embryogenic response. This allows to modulate embryo yield within a functional range, with lower and upper Ca2+ thresholds beyond which embryo yield is reduced. There seems to be a relationship between Ca2+ levels and embryo differentiation.